Current Challenges and Advances in Cataract Surgery - Shoji, Nobuyuki (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on new trials related to cataract surgery, intraocular lens power calculations for cataracts after refractive surgery, problems related to high myopia, toric IOL power calculations, etc. Intraoperative use of the 3D Viewing System and OCT, studies on the spectacle dependence of EDOF, IOL fixation status and visual function, and dry eye after FLAC are also discussed. Proteomic analysis of aqueous humor proteins is also discussed.